Effectiveness of clown therapy on procedural pain in children with cerebral palsy. A meta-analysis - Luca Giuseppe Re; Viviana Fusetti (Milano University Press, 2023)
BACKGROUND: Nearly 10% of the pain that affects children with cerebral palsy (CP) results from a medical procedure. Clown therapy is a popular distraction technique to reduce pain; some systematic reviews evaluate the efficacy of this intervention in the pediatric setting, but none on children with CP. AIM: To evaluate the effect of clown therapy on procedural pain in children with CP. METHODS: Systematic review with meta-analysis of clinical trials with control group. Retrieval of studies by querying biomedical databases, online resources and trial registers. Clown therapy was compared with standard care. The primary outcome was the pain level after surgery. The risk of bias was assessed with RoB 2. Effect size was calculated with a random effects model. RESULTS: Three studies with 164 patients were included. The risk of bias is high for two studies and raises some concerns for one. All studies analyzed the effect of clown therapy on procedural pain after botulinum toxin injection. There was a statistically non significant reduction in pain in the intervention group compared to the control group (SMD: -0.20, 95% CI: -0.56, 0.17). The heterogeneity between studies is high. CONCLUSION: Clown therapy for procedural pain from botulinum toxin injections in children with CP seems effective but the methodological limitations of the studies do not allow a definitive judgment. There is a lack of studies evaluating the effect of the intervention on other procedures that children with CP undergo periodically.